Structural Analysis and Design of Superstructure and Roof Systems for the Canteen Building at Kalimantan Institute of Technology - Hijriah; Fachreza Akbar; Andi Sahputra Depari; Amanda Sabina Putri; Suardi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Kalimantan Institute of Technology (ITK), established on October 6, 2014, in Balikpapan, East Kalimantan, currently lacks adequate canteen facilities, compelling the academic community to seek meals off-campus. This study aims to design a new canteen facility to be constructed above the campus reservoir, focusing specifically on the structural and roofing systems. The planned canteen is expected to fulfill the food and beverage needs of students, lecturers, and staff, while also serving as a hub for social interaction. Our research methodology incorporates both qualitative and quantitative approaches. The project phases encompass detailed load analysis, structural modeling, internal force analysis, and a thorough plumbing design. Structural design adheres to the relevant Indonesian National Standards (SNI) for reinforced concrete structures and earthquake resistance. The substructure utilizes deep foundations adapted to local soil conditions, while the superstructure comprises reinforced concrete elements and a steel roofing system. Structural analysis results indicate the use of beams B1 (500×300 mm) and B2 (400×200 mm), circular columns K1 (D600 mm), and slab thickness of 120 mm. The roof structure consists of IWF rafters (300×150×6.5×9 mm), HB columns (300×300×10×15 mm), and CNP 200–16. This integrated design demonstrates a feasible and sustainable approach to infrastructure development on water-saturated soils.